Environmental Influences on Dietary Intake of Children and Adolescents - Gubbels, Jessica S. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Childhood is a crucial period for establishing lifelong healthy nutritional habits. The environment has an important influence on children's dietary intake. This book focuses on the influence of environmental factors on the dietary intake of children and adolescents (0-18 years of age) within various settings including home, early care and education, school, college, holiday clubs, neighborhoods, and supermarkets. The reported studies examine a variety of factors within these settings, including the influence of cooking and parenting, teacher style, resources and barriers within various settings, marketing, and many other factors. The dietary intake behaviors examined include snacking, fruit and vegetable intake, beverage intake, and also nutrition in general. In addition, several papers focus on problems caused by inadequate nutrition, such as hunger and obesity. This work underlines the importance of the environment in influencing children's and adolescents' dietary intake. In addition, the papers identified some crucial barriers and facilitators for the implementation of environmental changes to enable a healthy diet for young children. Therefore, it provides some important directions for both future research and practice.